2017
DOI: 10.1155/2017/7375615
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Chemical Constituents Isolated from Artemisia iwayomogi on Polyol Pathway and Simultaneous Quantification of Major Bioactive Compounds

Abstract: Blocking the polyol pathway plays an important role preventing diabetic complications. Therefore, aldose reductase (AR) and advanced glycation endproducts (AGEs) formation has significant effect on diabetic complications. Artemisia iwayomogi has long been used as treatment of various diseases in Korea. However, no literatures have reported on AR and AGEs formation inhibitory activities of A. iwayomogi. For these reasons, we aimed to assess that A. iwayomogi had potential as anti-diabetic complications agents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Although AIE did not show higher inhibition of cell growth than that of sorafenib in HCC, we observed that AIE had capacity to inhibit cell growth of HCC with less cytotoxicity in normal cells. Scopoletin and isochlorogenic acid B are well-known compounds of AI as previously reported [14,15]. For this reason, these compounds were used to standardize AIE.…”
Section: Resultsmentioning
confidence: 99%
“…Although AIE did not show higher inhibition of cell growth than that of sorafenib in HCC, we observed that AIE had capacity to inhibit cell growth of HCC with less cytotoxicity in normal cells. Scopoletin and isochlorogenic acid B are well-known compounds of AI as previously reported [14,15]. For this reason, these compounds were used to standardize AIE.…”
Section: Resultsmentioning
confidence: 99%
“…The results are summarized in Table 2 . The IC 50 values of positive control in AChE, BChE, BACE1, and AGEs formations were judged suitable compared with previous literatures [ 16 , 26 , 27 , 34 ]. The M. officinalis extracts, Hx, and EA fractions significantly inhibited AChE activity (IC 50 of 58.82 ± 9.13, 33.66 ± 4.73, and 80.14 ± 16.65 μg/mL, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous varieties of phytoconstituents present in plants, including phenols, flavonoids and alkaloids, are responsible for the effective biological activities of plants, including antioxidant, anti-inflammatory, anti-atherosclerotic, anti-tumor, anti-bacterial and anti-viral effects (28). Compounds isolated from DJ exert pharmacological effects in a number of diseases and processes, including obesity, diabetes, fatty liver, inflammation and aging (23,29,30). However, to the best of our knowledge, no previous studies have reported the inhibitory activities of PDJ on macrophage cells for the treatment of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A. iwayomogi exerts various biological effects such as anti-oxidation, anti-inhibition and anti-inflammation, and has been widely used in the treatment of various diseases, including hepatitis, inflammation, cholecystitis and immune-related disorders (22). Methanolic extracts of A. iwayomogi have been shown to exhibit scavenging activity in a number of diseases involving inflammation, and to inhibit NO production by LPS-activated macrophages (23). However, the mechanism underlying the anti-inflammatory effect of DJ remains largely unknown.…”
Section: Artemisia Iwayomogi (Dowijigi) Inhibits Lipopolysaccharide-imentioning
confidence: 99%